PENGARUH JARAK TANAM TERHADAP PRODUKTIVITAS INDIGOFERA (Indigofera zolingeriana) DI AREAL TERBUKA - Morip, Wemiles; Anis, S.D.; Telleng, M.M.; Sumolang, C. I. J. (Universitas Sam Ratulangi, 2020)
The Effect of Planting Space On Productivity of Indigofera (Indigofera zollingeriana) in Full Sun Area. The purpose of this research was determines the productivity of Indigofera zollingeriana with three different planting space. This experiment was conducted using Completely Randomized Design (CRD). The treatment consisted of three planting space, (1) 1.0 m x 0.5 m, (2) 1.0 m x 1.0 m, and (3) 1.0 m x 1.5 m, each treatment had six replications. Data were analyzed using analysis of variance and HSD test. The variables measured were fresh and dried stem weight, fresh and dried leaf weight. The results showed that planting space were significant different (P<0.01) on fresh and dried stem weight, fresh and dried leaf weight. Â HSD test showed that planting space 1.0 m x 1.5 m were significant (P<0.01) have higher stem fresh weight, stem dry matter weight, fresh leaf weight and leaf dry matter weight than planting space 1.0 m x 1.0 m and 1.0 m x 0.5 m. It can be concluded that planting space 1.0 m x 1.5 m have the highest productivity that were highest stem freshweight, stem dry matter weight, leaf freshweight and leaf dry matter weight.Key words: Indigofera zollingeriana, planting space, productivity